(untitled) (Jurnal Pendidikan Islam, 2014)
The issue of women is still a serious discourse for discussion, both about the identity, position and role, even to the character and intellect. This article discusses the theory of education and emancipation of women in view of Abbas Mahmud al-‘Aqqad, an Egyptian thinker, poet, philosopher and journalist scholars in the late - 19th and early 20th century. According to Him, women have equal footing with men in education and all social roles. But the natural differences between women and men demanding the division of different roles, so that the relationship of women and men should be a partnership. Conservative viewsof ‘ Aqqad theory based on the Koran, the Hadith and the research on the female characters. This theory is in line with structuralist functionalist theory. Structuralist theory gravitate to sociology, while learning functionalist psychological theory, but they have same conclusion, that the relationship of women and men is the preservation of harmony, not competition. ‘Aqqad’stheory could be a solution to the issue of family crisis and child neglect that often occurs as a result of the division of the marital partnership roles are less than ideal.